Gender Alert: No Excuse - Calling for an End to Gender-based Violence in Sudan - United Nations Women (United Nations, 2024)
More than 11 million people have been displaced amid the conflict in Sudan as of October 2024, with more than half (54 per cent) being women and girls. An estimated 12 million people are currently at risk of gender-based violence, as described in this new Gender Alert by UN Women. Documented cases of mass and systemic rape highlight the use of sexual violence as a weapon of war, leaving survivors in dire need of medical, psychological, and social support. Since December 2023, the number of survivors of gender-based violence, including conflict-related sexual violence, seeking services increased by 288 per cent, illustrating the scope of the crisis. Evidence shows that women and girls from ethnic minority groups are being deliberately targeted.